2008
DOI: 10.1161/hypertensionaha.107.107219
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Tempol Prevents Hypertension, Proteinuria, and Poor Feto-Placental Outcomes in BPH/5 Mouse Model of Preeclampsia

Abstract: Abstract-Recently we described a mouse model, BPH/5, that spontaneously develops the hallmark clinical features of preeclampsia. BPH/5 exhibit impaired placentation before the onset of hypertension and proteinuria, supporting a causal role for the placenta in the pathogenesis of preeclampsia. Here we tested the hypothesis that an increase in reactive oxygen species (ROS) early in pregnancy results in placental abnormalities leading to the maternal symptoms of preeclampsia. We further hypothesized that chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 48 publications
5
63
0
Order By: Relevance
“…Placental oxidative stress has been shown to be increased in preeclamptic women, and placental and renal oxidative stress is observed in preclinical models preeclampsia, and it is implicated in contributing to the development of vascular dysfunction, proteinuria, and hypertension during pregnancy (9,13,27,28). Importantly reactive oxygen species (ROS) is a byproduct of inflammation and is elevated in response to RUPP CD4ϩ T cells and IL-17-and AT 1 -AA-induced hypertension during pregnancy.…”
Section: Np T Reg Cell Supplementation Normalizes Tgf-␤ In Rupp Ratsmentioning
confidence: 99%
“…Placental oxidative stress has been shown to be increased in preeclamptic women, and placental and renal oxidative stress is observed in preclinical models preeclampsia, and it is implicated in contributing to the development of vascular dysfunction, proteinuria, and hypertension during pregnancy (9,13,27,28). Importantly reactive oxygen species (ROS) is a byproduct of inflammation and is elevated in response to RUPP CD4ϩ T cells and IL-17-and AT 1 -AA-induced hypertension during pregnancy.…”
Section: Np T Reg Cell Supplementation Normalizes Tgf-␤ In Rupp Ratsmentioning
confidence: 99%
“…19 Confocal images were analyzed by morphometric analysis of pixels per nucleus using MetaMorph software Version 7 (Molecular Devices). The color threshold was set the same for each image, and the red pixel density was obtained by dividing the total pixel density value by the number of nuclei in the smooth muscle and endothelial layers or renal cortex.…”
Section: Assays For Rosmentioning
confidence: 99%
“…Gestational hemodynamic data from radiotelemetric studies have been reported for normal rats 28,29 and normal B6 mice, 30,31 but none of these publications provide fully characterized hemodynamic profiles for normal animals, particularly using continuous radiotelemetry. Nishizawa et al 32 compared SAP and DAP using indirect tail-cuff measures between syngenically (B6ϫB6) and allogeneically mated (B6ϫBALB/c) mice from gd7 to gd17.…”
Section: Burke Et Al Spiral Artery Remodeling and Mouse Gestational Mapmentioning
confidence: 99%